The study of efficacy of injection iron sucrose in treatment of iron deficiency anemia in pregnancy - Singh, Akhileshwar; Singh, Sanjay; Sharma, Anuj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Iron deficiency is the most common cause of anaemia in pregnancy amounting to almost 50% of pregnant ladies in India. All pregnant women, irrespective of haemoglobin status, should receive prophylactic doses of iron from second trimester. Iron sucrose has an advantage of being cost effective and readily available. The objective of this was to study the efficacy of injection Iron Sucrose in treatment of iron deficiency anaemia in pregnancy. Methods: About106 patients were given in injection iron sucrose in pregnancy, who had intolerance to oral iron or were non-compliant, in pre calculated (Ganzoni’s formula) doses and were followed up with rise in hemoglobin and ferritin after 6 weeks and at term. Results: Statistically significant increase in hemoglobin levels was observed at 6 weeks after initiation of treatment (9.689±0.821 gm% vs 10.906±0.775 gm%) as well as at term (mean 10.981±0.690 gm%). The serum ferritin levels too increased significantly at term (26.7 ng/mL±12.92 vs 65.34 ng/mL±15.73). Conclusions: Present study demonstrates that iron sucrose is an excellent option to treat iron deficiency anemia in patients where oral iron therapy has either failed or not suitable. It significantly increases hemoglobin levels in the study population. It is readily available in the market and can be infused on an outpatient basis.